The best way to drink in Beja and beyond: Water and milk - (:unkn) unknown (My University, 2021)
In the Beja society of the eastern arid zone of Sudan, water and milk are essential beverages for survival, and are also salient elements of the culture reflected in a rich lexicon. This paper shows how social rules, time intervals, and incompleteness are encoded in monolexemic drinking and milking items, as well as lexical differences based on the animacy hierarchy between humans and animals in the domain of thirst. The Beja lexical structure is compared with that of other African languages, and the Beja social rules related to drinking and milking are illustrated with two anecdotes extracted from pieces of oral literature.
Keywords: African Research